International Cooperation to Enable the Diagnosis of All Rare Genetic Diseases - Boycott, Kym M; Rath, Ana; Chong, Jessica X; Hartley, Taila; Alkuraya, Fowzan S; Baynam, Gareth; Brookes, Anthony J; Brudno, Michael; Carracedo, Angel; den Dunnen, Johan T; Dyke, Stephanie O M; Estivill, Xavier; et al. (American journal of human genetics, 2017)
Provision of a molecularly confirmed diagnosis in a timely manner for children and adults with rare genetic diseases shortens their "diagnostic odyssey," improves disease management, and fosters genetic counseling with respect to recurrence risks while assuring reproductive choices. In a general clinical genetics setting, the current diagnostic rate is approximately 50%, but for those who do not receive a molecular diagnosis after the initial genetics evaluation, that rate is much lower. Diagnostic success for these more challenging affected individuals depends to a large extent on progress in the discovery of genes associated with, and mechanisms underlying, rare diseases. Thus, continued research is required for moving toward a more complete catalog of disease-related genes and variants. The International Rare Diseases Research Consortium (IRDiRC) was established in 2011 to bring together researchers and organizations invested in rare disease research to develop a means of achieving molecular diagnosis for all rare diseases. Here, we review the current and future bottlenecks to gene discovery and suggest strategies for enabling progress in this regard. Each successful discovery will define potential diagnostic, preventive, and therapeutic opportunities for the corresponding rare disease, enabling precision medicine for this patient population.
Keywords: Exome; genom lidský; Matchmaker Exchange; mezinárodní spolupráce; gene discovery; Rare Diseases; vzácné nemoci; International Cooperation; disease modeling; exom; rare diseases; Genome, Human; ontologies; databáze faktografické; Humans; solving the unsolved; IRDiRC; transcriptome sequencing; genome sequencing; Databases, Factual; lidé